An Annotated Catalog of the Iranian Berytidae and Piesmatidae (Hemiptera: Heteroptera: Pentatomomorpha: Lygaeoidea) - Ghahari, Hassan; Moulet, Pierre (Zootaxa, 2012)
A list of Iranian Berytidae and Piesmatidae (Heteroptera: Lygaeoidea), with 25 species (16 species of Berytidae and 9 species of Piesmatidae), is given in this paper. Apoplymus pectoralis Fieber 1859, Berytinus clavipes (Fabricius 1775) (both Berytidae), Parapiesma kochiae (Becker 1867), and P. tenellum (Horváth 1906) (both Piesmatidae) are reported as new records for Iran.